Vascular anatomical considerations in preparing colonic flaps to replace the oesophagus - Amr Abdelhamid AbouZeid (Annals of Pediatric Surgery, 2021)
Abstract Background The colon is among the best options to substitute the oesophagus; it is well known for its durability and good function that makes it most suitable for paediatric patients. The steps of the procedure, postoperative complications, and outcome assessment were thoroughly discussed in previous reports. However, in this report, we have tried to focus on one basic and essential step of the operation, which is fashioning of the colonic flap used to substitute the oesophagus. Results The study included 50 consecutive paediatric cases who underwent colonic replacement of the oesophagus during the period 2010 through 2020. The indication for oesophageal replacement was either oesophageal atresia (27 cases) or corrosive strictures (23 cases). Our standard technique was using a middle segment of the colon (transverse colon) based on the left colic vessels (vascular pedicle) after ligation of middle colic vessels. Variations of the middle colic vessels were encountered that included single, double, or absent vessels. In a single case (2%), the middle colic vessels were multiple, short, and non-branching with interrupted continuity of marginal vessels at that point. In the latter situation, we had to use a different technique by fashioning a right colonic flap based on the middle colic vessels. Conclusion In colonic replacement of the oesophagus, preparing a pedicled flap from the transverse colon based on the left colic vessels was almost always feasible owing to the stable collateral marginal vessels. On a rare occasion, the marginal vessels were interrupted by disturbed anatomy of the middle colic vessels when we had to shift to another technique using a right colonic flap.